TINJAUAN MAQASHID SYARIAH TERHADAP KONSUMSI - Annisa Masruri Zaimsyah; Sri Herianingrum (Ulumuna: Jurnal Studi Keilsman, 2019)
The purpose of this paper to look at consumer ethics in the view of maqasid sharia, because of the high level of consumption of a Muslim who is not in accordance with Islamic principles. In consuming a Muslim must also look at the maslahah of the products consumed. Maqasid sharia is the basis for a Muslim to consume halal food. Maqosid sharia is very necessary to be described so as to provide an understanding of the rationale based on sharia for humanity to live according to Islamic law. In consuming consumer behavior, it must be based on what has been regulated by Islamic law, namely: consuming Halal and Service Goods which are permitted which are clearly halal and haram, consumption for life in the world and the hereafter, paying attention to expenditure patterns so that income and expenditure are balanced, unlimited human desires but consumption must be balanced, a standard of living that is simple and not extravagant, does not accumulate wealth, and considers halal and haram what is consumed. So that to meet primary, secondary and tertiary needs must be in accordance with Islamic principles.